Designing Windows Based Learning Applications Using Biology Material (Viruses) - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Sitorus, Andika; Nazwa, Safira; Calista, Sandha (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
In the current era of computers and the internet, the use of technology in education is becoming increasingly important to increase the efficiency and effectiveness of the learning process. In this article, we will learn how to create a Windows-based learning application using the Visual Studio Framework and the Visual Basic programming language. By providing interactive and easy-to-use tools, this application is intended to support the educational process. User needs analysis is the main stage in the application design process, such as system design, implementation, and testing. User needs analysis is carried out to determine the special needs of teachers and students, such as managing learning materials, monitoring learning progress, and evaluation. System design also includes application architecture and user interfaces that enable easy and effective interaction. The research results show that this Windows-based learning application has the ability to improve interaction between teachers and students, facilitate access to learning materials, and provide useful evaluation tools. However, issues such as hardware compatibility and user training requirements were also discovered. As a result, it is hoped that this application can help learning in the digital era while development continues to be carried out to overcome existing problems.